Effect of Citric Acid Concentration and Boiling Time on Physicochemical Properties of Passion Fruit Jelly Drink - Merynda Indriyani Syafutri; Herlianah; Tri Wardani Widowati; Friska Syaiful; Eka Lidiasari; Anny Yanuriati; Citra Pratiwi Prayitno (Prodi Teknologi Hasil Pertanian Universitas Sriwijaya, 2024)
The objective of this research was to learn the physical and chemical properties of passion fruit jelly drink with difference of citric acid concentration and boiling time. This research used a Factorial Completely Randomized Design with two treatment factors and three replications. First factor was the concentration of citric acid and second factor was boiling time. The observed parameters were physical properties (texture, viscosity, color), and chemical properties (total acidity, total dissolved solids, flavonoid, pH). The results showed that the concentration of citric acid significantly decreased value of texture, viscosity and pH, and increased value of chroma, total acidity and total dissolved solids. Boiling time had significant effects on increased value of texture, viscosity, total acidity and total dissolved solids. The interaction of citric acid concentration and boiling time had significant effect on increased value of total acidity. The best treatment was passion fruit jelly drink with a concentration of 0.3% citric acid addition, and a boiling time of 10 minutes.